Toxoplasma gondii infection induces dendritic retraction in basolateral amygdala accompanied by reduced corticosterone secretion - Vyas, Ajai (2013)
Pathological anxiety is thought to reflect a maladaptive state characterized by exaggerated fear. Naturally occurring perturbations that reduce fear can be crucial in the search for new treatments. The protozoan parasite Toxoplasma gondii invades rat brain and removes the fear that rats have of cat odors, a change believed to be parasitic manipulation of host behavior aimed at increasing parasite transmission. It is likely that mechanisms employed by T. gondii can be used as a heuristic tool to understand possible means of fear reduction in clinical settings. Male Long-Evans rats were infected with T. gondii and compared with sham-infected animals 8 weeks after infection. The amount of circulating plasma corticosterone and dendritic arborization of basolateral amygdala principal neurons were quantified. Previous studies have shown that corticosterone, acting within the basolateral amygdala, enhances the fear response to environmental stimuli. Here we show that T. gondii infection causes a dendritic retraction in basolateral amygdala neurons. Such dendritic retraction is accompanied by lower amounts of circulating corticosterone, both at baseline and when induced by an aversive cat odor. The concerted effects of parasitism on two pivotal physiological nodes of the fear response provide an animal model relevant to interactions between stress hormones and amygdalar plasticity.